2017
DOI: 10.1016/j.jor.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Unstable acromioclavicular joint injuries: Is there really a difference between surgical management in the acute or chronic setting?

Abstract: Level III, retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…A recent study by Natera et al also suggests that there are no significant differences between acute and chronic repair of AC joint dislocations if all other aspects of treatment are similar. 14…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Natera et al also suggests that there are no significant differences between acute and chronic repair of AC joint dislocations if all other aspects of treatment are similar. 14…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have recommended using the ISAKOS subdivision for imaging evaluation throughout the decision-making process for evaluating AC joint injuries. 3 , 17 , 18 , 27 , 30 , 31 , 34 Recently, the panel members of the European Society of Sports Traumatology, Knee Surgery & Arthroscopy agreed that the Rockwood classification, modified by the ISAKOS statement, is the most appropriate and comprehensive classification to date to guide treatment choice. 40 However, to our knowledge, no study has shown the reliability of categorizing AC joint injuries using the ISAKOS proposal.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have adopted this new approach in their clinical practice, 3 , 17 , 18 , 27 , 30 , 31 , 34 and it has been accepted as a comprehensive classification system. 40 However, the reliability of the modified classification has not been demonstrated.…”
mentioning
confidence: 99%
“…Type I and II injuries are typically treated nonoperatively owing to partial injury to the AC and/or CC ligaments, whereas type IV to VI injuries are most often treated surgically owing to complete disruption of the AC and CC ligaments leading to instability, pain, and disability 2 . Treatment of type III injuries remains controversial, with a trend toward nonoperative management and rehabilitation 3, 4, 5. The ISAKOS Terminology Project suggested a revision to the Rockwood classification by further subdividing the type III AC joint injuries into type IIIA (stable) and type IIIB (unstable) 6 .…”
mentioning
confidence: 99%
“… 2 Treatment of type III injuries remains controversial, with a trend toward nonoperative management and rehabilitation. 3 , 4 , 5 The ISAKOS Terminology Project suggested a revision to the Rockwood classification by further subdividing the type III AC joint injuries into type IIIA (stable) and type IIIB (unstable). 6 Type IIIA injuries are defined as those with no overriding of the clavicle on a cross-body abduction radiograph and with no significant scapular dysfunction, whereas unstable type III injuries demonstrate therapy-resistant scapular dysfunction and persistent pain after 3 to 6 weeks of conservative management with overriding of the clavicle on the cross-body abduction radiograph.…”
mentioning
confidence: 99%